Optimization of Coagulation and Flocculation in Concrete Wastewater of Precast Industry - Ni Iluh Permata Ariase; Temmy Wikaningrum (President University, 2021)
Abstract. The population increase until the end of 2019 reached 267 million. This is in line with developments that support activities. This is inseparable from the actions of one of the precast concrete companies PT.WB Precast Plant Karawang in supporting development that produces waste in the form of wastewater. The parameter measured as a reference in carrying out processing is the Minister of Health Regulation Number 32 of 2017. This study's method refers to turbidity as a physical parameter, namely 25NTU and hardness total as a chemical parameter, which is 500 mg / l. CaCO3. Objectives: The purpose of this study was to determine the optimization of the use of PAC as a coagulant and flocculant to reduce the turbidity and total hardness and determine the optimum detention time of flocculation. Method and results: The sampling method in this study is observation. The population in this study is concrete wastewater with parameter values that are not in accordance with the standard. Conclusion: By using PAC 10% the optimum doses is 140 ppm, and the optimum detention time of flocculation is 5 minute that can reduce the turbidity from 275 NTU to be 11.615 NTU or 95.7% and can reduce total hardness from 948.75 mg/l CaCO3 to be 491.25 mg/l CaCO3 or 48.2%.